Practice and Challenges of Online Science Teaching at Higher Education During COVID-19 Pandemic - Yadav, Rajeswer Prasad (Orchid Academia Siraha, 2022)
The education system is adversely affected by COVID-19 pandemic in Nepal. This study particularly focused to find the existing ICT competencies of science teachers in online teaching-learning and challenges faced to teach during COVID-19. The study followed the quantitative descriptive research design in which all teachers of science of constituent and affiliated campuses of Siraha that run science and technology and science education were selected through census method. A total of 36 science teachers were selected from 3 campuses, one constituent, two affiliated campuses. Closed and structured questionnaires were also used for the collection of data. The obtained data were interpreted by using statistical tools like percentage, mean, standard deviation, correlation, significance through spearman's rho rank order correlation coefficient, bivariate analysis between independent and dependent variables by using Statistical Package for Social Science (SPSS) version 20.The result showed that almost all teachers had basic requirement of ICT tools and their operating knowledge. One-third had ICT training/ certificate of ICT but only below 20 percentages really practiced it in teaching-learning. The traditional concept of physical mode of teaching, ICT infrastructures, poor ICT capacity, lack of incentives and in adequate ICT friendly environment are major challenges for effective online teaching.